Anc Bed For Preeclamsi Early Detection Using Web System - Fiqih Fahrur Ramadhan; Andjar Pudji; Muhammad Ridha Mak’ruf; Shubhrojit Misra (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
One of the causes of the high maternal mortality rate is dominated by three factors, one of which is preeclampsia. Preeclampsia is a condition in which the mother experiences hypertension and changes in BMI (Body Mass Index) at the 20th week of gestation. Preeclampsia indications in pregnant women are related to examinations, namely Antenatal care (ANC). Antenatal care is one of the prenatal checks with certain standards. Pregnant women need extra antenatal supervision from health workers. Preeclampsia detection carried out in health care facilities is currently considered to be still not optimal so that there are still many cases of preeclampsia that are not handled properly. One of the efforts that can be made to improve services for pregnant women is with a web-based ANC examination. The purpose of this study is to analyze NIBP and BMI data sent and received by IoT media so that they are useful for the diagnostic process. The contribution of this research is knowing the response of NIBP and BMI data sent and received via IoT media. The procedure for achieving this goal is with the MPX5050 sensor and Loadcell whose output will be processed and displayed on a web page. From this study it can be concluded that the sending of IoT-based NIBP and IMT data affects lost data or delays received. The findings from this study are expected to be developed in further research. So that it can be said that the use of the ESP32 module as the delivery of ANC BED inspection results resulted in no loss of data found in sending ANC inspection results with 100% data results being sent without any data loss and delay with an average of 2 seconds.